Communicating Terror: Mediatization and Ritualization. (February 2018) - Cui, Xi; Rothenbuhler, Eric
In this essay, we explicate the internal logic of contemporary terrorist acts and our society's responses, to denaturalize the label and meanings we give to "terrorism." We argue that contemporary terrorism communicates intimidation, fear, and anxiety through the ritualization and mediatization of terrorist attacks. Mediatization refers to the strategic coercion of imperative media coverage of the attacks, and ritualization refers to the focus on sacred life structures in both terrorist attacks and remedial responses. In combining ritualization and mediatization, terrorism aims to introduce maximal chaos through unexpected disruption of the sacred and taken-for-granted in everyday life in the community of the attack and wherever media coverage can reach. The fear and anxiety induced by disrupted life rhythms, including normal media flows, and the compelling footage of the disruption lead to ritualized reactions which both restore and transform the social order beyond the moment of the attack.